2010
DOI: 10.2147/ppa.s11934
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and initial treatment decisions for patients with schizophrenia at risk of treatment nonadherence

Abstract: In this year-long, prospective observational study, sociodemographic, clinical, and functional characteristics were assessed in outpatients with schizophrenia from Australia, Mexico, Romania, and Taiwan who were switched from their primary oral antipsychotic to another oral or depot antipsychotic at study entry because of physician-perceived nonadherence risks. Patients (N = 406) rated their quality of life and functioning level as low. Few patients (10.6%, 43/406) were switched to depot antipsychotics, with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
(64 reference statements)
1
15
1
Order By: Relevance
“…Furthermore, a recent metaanalysis has shown that the efficacies of moderately low and standard doses are comparable in preventing relapse in schizophrenia (Uchida et al, 2011). In contrast, the findings in the present study suggest that when dose reduction is attempted, caution must be exercised in light of potential relapse for patients with severe psychopathology such as those who require depot antipsychotics for many reasons (Shi et al, 2007;Kelin et al, 2010). It was found that although the very low-dose treatment increased the chance of relapse, the low-dose treatment was as effective as the standard-dose treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, a recent metaanalysis has shown that the efficacies of moderately low and standard doses are comparable in preventing relapse in schizophrenia (Uchida et al, 2011). In contrast, the findings in the present study suggest that when dose reduction is attempted, caution must be exercised in light of potential relapse for patients with severe psychopathology such as those who require depot antipsychotics for many reasons (Shi et al, 2007;Kelin et al, 2010). It was found that although the very low-dose treatment increased the chance of relapse, the low-dose treatment was as effective as the standard-dose treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Figure 1 provides an overview of patient disposition at study entry, which has previously been reported in detail 21. Of the 440 patients considered to be at risk of nonadherence and who entered the study, 406 patients were enrolled (Australia, n = 64; Mexico, n = 40; Romania, n = 156; Taiwan, n = 146).…”
Section: Resultsmentioning
confidence: 99%
“…Patient sociodemographic characteristics at study entry have been reported in detail 21. Patients were in their late 30s (mean ± SD, 37.2 ± 10.2 years), mostly male (56.7%, 230/406), and had a mean ± SD BMI of 26.1 ± 5.56 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This post hoc analysis used data from a 1‐year, prospective observational study that assessed all‐cause medication discontinuation in outpatients with schizophrenia who were considered by their physicians to be at risk of non‐adherence (25). The primary objective was to compare all‐cause medication discontinuation (any switch, augmentation or medication discontinuation) in matched cohorts of patients who were initiated on depot or oral antipsychotics at study entry.…”
Section: Introductionmentioning
confidence: 99%